(untitled) (Mongolian Journal of Agricultural Sciences, 2020)
Field tests of a modified seed drill SZP-3.6 for sowing small-seeded crop (Сamelina sativa) were carried out and the depth of seeding, interrow spacing and the number of plants per 1 m square area were determined. Results of the testing parameters were developed by mathematical statistics method. A pilot arrangement of Luoyang LT-850+SZP-3.6 was used. Estimated drag force of attachment was Rт=205.8±40.62kg. With inter row and plant spacing at 14.87± 3.5cm and 4.64± 1.69 cm, respectively, and 21 plants in 1 m long single row, the agro-technical requirements for both attachment and plants are fully met. The measurement of performance of arrangement: Luoyang LT-850+SZP-3.6, provides an average seeding depth at h ̅=2.78cm, with mean deviation at σ_х=±0.81cm. This is 28% higher than the given agrotechnical requirement of 2cm. Moreover, an average plant density at 86±13 per m2, and 860 thousand plants per ha fall within the limits in the view of soil nutrients distribution. СЗП-3,6 үрлүүрийг жижиг үрт таримал тариалахад зориулан тоноглож туршсан дүн Жижиг үрт таримал Камилина сативаг (Сamelina sativa) тариалахад зориулж үр тарианы СЗП-3,6 үрлүүрийг үрлэх аппарат, үрийн хоолой, сошникний чиглүүлэгч болон мөр дагаж булдах булаар тоноглож талбайд туршив. Угсрааны агротехнологийн үзүүлэлтүүдийг туршилтаар тогтоож үр дүнг математик статистикийн аргаар боловсруулахад таримлын мөр хоорондын зай үр суух гүн 2.51 см, үрлүүрийн чангаах эсэргүүцэл кг, таримлын мөр хоорондын зайн дундаж утга см, ургамал хоорондын зайн утга нь см байв. Түлхүүр үг: үрлүүр, катушкин үрлэх аппарат, сошник, бул, жижиг үрт таримал